2011
DOI: 10.1186/bcr3039
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the phosphatidylinositol 3-kinase pathway: role in tumor progression and therapeutic implications in breast cancer

Abstract: Mutations in genes that constitute the phosphatidylinositol 3-kinase (PI3K) pathway occur in >70% of breast cancers. Clinical and experimental evidence suggest that PI3K pathway activation promotes resistance to some of the current breast cancer therapies. PI3K is a major signaling hub downstream of human epidermal growth factor receptor (HER)2 and other receptor tyrosine kinases. PI3K activates AKT, serum/glucocorticoid regulated kinase (SGK), phosphoinositide-dependent kinase 1 (PDK1), mammalian target of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
305
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(331 citation statements)
references
References 115 publications
6
305
2
2
Order By: Relevance
“…Tumours of this subtype are in general hormone responsive with low proliferation rate and associated with a relatively good prognosis. Alterations in the PI3K/AKT pathway, mainly PIK3CA mutations, have been shown most frequent in the luminal subtypes, suggesting a crosstalk between ER and PI3K/AKT [3]. Aberrant PI3K/AKT signalling has been connected to poor response to anti-oestrogen therapies in several studies [20,[42][43][44][45][46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumours of this subtype are in general hormone responsive with low proliferation rate and associated with a relatively good prognosis. Alterations in the PI3K/AKT pathway, mainly PIK3CA mutations, have been shown most frequent in the luminal subtypes, suggesting a crosstalk between ER and PI3K/AKT [3]. Aberrant PI3K/AKT signalling has been connected to poor response to anti-oestrogen therapies in several studies [20,[42][43][44][45][46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…In malignant cells, this pathway is commonly overstimulated and genetic and epigenetic alterations of the PI3K/AKT pathway are suggested as one driving cause of tumour development and progression [1,2]. In breast cancer, common aberrations include mutations in the PIK3CA and AKT genes, overexpression or activation of several upstream growth factors and receptor tyrosine kinases as well as loss of function of negative regulators, e.g., the phosphatase and tensin homologue (PTEN) [2,3]. Enhanced activation of the PI3K/AKT pathway has been suggested as a useful prognostic and treatment predictive factor in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in vitro, mammary tumor cells derived from PyMT:Irs-1 ÏȘ/ÏȘ tumors have enhanced PI3K/mTor signaling, and this increased activity is dependent upon Irs-2 (14). The PI3K signaling pathway is one of the most commonly mutated pathways in cancer, including breast cancer (23,24). PI3K itself is an oncogene, and activating mutations have been observed in many types of cancer (25).…”
mentioning
confidence: 99%
“…This class II phosphatase is one of the many players involved in the negative regulation of phosphatidylinositol signaling, a pathway of particular interest for targeted therapies in basal-like and triple-negative breast cancers. [144][145][146][147][148] Located on chromosome 4q31.21, the INPP4B locus is commonly deleted in basal-like breast cancers and cell lines. [92][93][94][149][150][151] Previous studies characterizing INPP4B as a tumor suppressor were primarily focused at the genetic level; however, Gewinner et al 93 recently demonstrated successful immunohistochemical analysis of INPP4B and correlation between loss of INPP4B expression and decreased overall breast cancer survival.…”
Section: Discussionmentioning
confidence: 99%